(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Family, often considered the cornerstone of society, plays a pivotal role in shaping the future. As we navigate the complexities of the modern world, it becomes crucial to instill national values in student youth, equipping them with the necessary skills and principles to build strong, resilient families. National values serve as the bedrock of a society, providing a shared set of beliefs, ethics, and principles that bind its people together. These values, rooted in the cultural and historical fabric of a nation, offer a framework for individuals to navigate life’s challenges. By instilling these values in student youth, we not only contribute to the preservation of a nation’s identity but also lay the foundation for the creation of stable and nurturing family environments.